2003
DOI: 10.1103/physrevlett.91.166104
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluidics: Viscous Dissipation in Layered Liquid Films

Abstract: We studied the layer-by-layer collapse of molecularly thin films of a model lubricant confined between two atomically smooth substrates. The dynamics of the consecutive expulsion of four molecular layers were found to slow down with decreasing film thickness but showed no evidence for confinement-induced solidification. Using a hydrodynamic model, we show that the sliding friction of liquid layers on top of the solid substrates is approximately 18 times higher than the mutual friction between adjacent liquid l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
106
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(124 citation statements)
references
References 29 publications
17
106
1
Order By: Relevance
“…More recent experiments have provided additional insights into this debate; several studies have found results consistent with the work of Klein and Kumacheva [13][14][15] while others have shown agreement with the conclusions of Granick 16,17 . Atomic force microscopy (AFM), with a much smaller contact area than SFB and SFA, has also been applied to study the confinement of organic fluids [18][19][20] .…”
Section: Introductionsupporting
confidence: 67%
“…More recent experiments have provided additional insights into this debate; several studies have found results consistent with the work of Klein and Kumacheva [13][14][15] while others have shown agreement with the conclusions of Granick 16,17 . Atomic force microscopy (AFM), with a much smaller contact area than SFB and SFA, has also been applied to study the confinement of organic fluids [18][19][20] .…”
Section: Introductionsupporting
confidence: 67%
“…The series of images presented on Fig. 3, which illustrates a transition from 5 to 4 layers, therefore shows a "squeeze-out front", as observed by Becker and Mugele (BM) [26].…”
Section: Outward Frontsmentioning
confidence: 69%
“…We now analyze in greater detail these results on squeeze-out front dynamics in order to (i) compare them quantitatively with those from BM [26], and (ii) check their consistency with the results obtained from the drainage experiments described in section III A.…”
Section: Outward Frontsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this behavior of the conservative forces is well understood and has also been reproduced for nanoscale contacts in early Atomic Force Microscopy (AFM) experiments [8], the dissipative behavior of nano-confined liquid films is heavily debated. In the SFA community, slightly different measurement techniques for nominally identical systems produced highly incompatible experimental results with interpretations ranging from confinement-induced solidification [9] or a glassy response [10] to bulk-like dynamics for liquid films of even just a few molecular layers thickness [11][12][13]. SFA measurements are limited to film thicknesses of integer numbers of molecular layers due to a mechanical (''jump-to-contact'') instability.…”
Section: Introductionmentioning
confidence: 99%